Effects of exercise interventions on breast cancer-related endogenous hormones in premenopausal and postmenopausal women: a systematic review and meta-analysis - He, Bo; Yu, Xiaomei (Frontiers in Physiology, 2025)
BackgroundBreast cancer is the most common malignant tumor among women, and its etiology and progression are closely associated with hormone levels. Hormone levels undergo significant changes in pre- and postmenopausal women. Exercise intervention, as a safe and effective lifestyle intervention, may modulate hormone levels and affect the incidence and prognosis of breast cancer.MethodsThree databases were searched to identify relevant literature for this study, which included 11 studies in the meta-analysis. The impact of an exercise intervention on breast cancer-related hormones was evaluated, including estrone, estradiol, free estradiol, testosterone, SHBG, 2-OH E1, 16a-OH E1, androstenedione, testosterone, and free testosterone, in both pre- and postmenopausal women.ResultsThe study findings suggest that the impact of exercise intervention on breast cancer-related hormones in pre- and postmenopausal women may not be significant. This lack of significance could be linked to differences in exercise intervention protocols, study quality, changes in body fat percentage post-exercise, and the specific characteristics of the populations (pre- and postmenopausal) analyzed in the studies. However, subgroup analyses suggested that exercise intervention might have a significant effect on certain estrogens in postmenopausal women and women who engaged in exercise for more than 6 months.ConclusionThe impact of exercise intervention on hormone levels may be influenced by body fat and menopausal status, as well as the duration of follow-up. Further high-quality and standardized studies are needed to confirm and enhance the findings of this research.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024430643, Identifier CRD42024430643.